Helminth fauna of the Eurasian beaver in the Czech Republic with remarks on the genetic diversity of specialist Stichorchis subtriquetrus (Digenea: Cladorchiidae) - Benovics, M; Reslová, N; Škorpíková, L; Seidlová, L; Mikulka, O (Parasitology research, 2022)
Eurasian beaver (Castor fiber) is a well-established faunal element in the Czech Republic, even though, historically, its populations were almost eradicated in this region. Nowadays, its distribution and population density are well monitored; nonetheless, the beaver's parasites, as potential threats to the environment, are often neglected in wildlife management. Therefore, we investigated the endoparasitic helminth diversity of 15 beaver individuals from three collection sites in the Czech Republic. Three parasite species were collected: Stichorchis subtriquetrus (Digenea), Travassosius rufus, and Calodium hepaticum (Nematoda), of which the two nematode species were reported for the first time from C. fiber in the Czech Republic. The highest prevalence and intensity of infection were observed in S. subtriquetrus (P = 93%, I = 1-138), while the two other species were collected only from one beaver individual. Subsequent analysis of the genetic diversity of the specimens using highly variable genetic markers revealed a weak population structure among the individuals collected from different beaver hosts. There was only a weak association of COI haplotypes with geography, as the haplotypes from the Berounka basin formed homogeneous groups, and individuals from the Dyje basin and Morava partially shared a haplotype. Even though common population genetic markers (i.e., microsatellites) did not reveal any structure in the hosts, our results suggest that the genetic diversity of their parasites may shed more light on population partition and the historical migration routes of Eurasian beavers.
Keywords: Genetic diversity; Parasite spill-over; genetická variace; Humans; Population genetics; Trichostrongyloidea; lidé; Trematoda; Czech Republic; Česká republika; Animals; Rodentia; hlodavci; Genetic Variation; zvířata; Reintroduction